2022
DOI: 10.1111/jocd.15218
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hair loss after COVID‐19: A systematic scoping review

Abstract: Objective While there are literature reporting increased incidence of hair loss in COVID‐19 patients, insufficient evidence exists on the topic to date. This review aims to identify the existing evidence and clinical characteristics of hair loss with COVID‐19 infection. Methods Following the PRISMA Extension for Scoping Reviews, MEDLINE and EMBASE were searched for all peer‐reviewed articles with relevant keywords including “Alopecia,” “Telogen Effluvium (TE),” and “COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 48 publications
5
23
1
6
Order By: Relevance
“…Meanwhile, Babaei et al in their study on TE following COVID-19 infection in Iran, found androgenetic alopecia as the most common concomitant pattern with TE [14]. Another study on hair loss post COVID-19 infection reported majority cases of TE and only few cases of alopecia areata and brosing alopecia [11]. We noted a relatively higher percentage of patterned hair loss, possibly because of high prevalence of pre-existing patterned hair loss in our study population.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Meanwhile, Babaei et al in their study on TE following COVID-19 infection in Iran, found androgenetic alopecia as the most common concomitant pattern with TE [14]. Another study on hair loss post COVID-19 infection reported majority cases of TE and only few cases of alopecia areata and brosing alopecia [11]. We noted a relatively higher percentage of patterned hair loss, possibly because of high prevalence of pre-existing patterned hair loss in our study population.…”
Section: Discussionsupporting
confidence: 39%
“…Alopecia areata (including totalis and universalis) may be exacerbated or induced by COVID-19 infection. Fibrosing alopecia has also been reported as isolated cases [4,11]. The mechanisms of hair loss remain unclear, although autoimmune abnormalities, immune imbalances and prolonged residual infection of hair follicle may be involved [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hair loss is also a PCC symptom associated with autoimmune and acute diseases including various viral infections. Hair loss after COVID-19 appears after approximately two months, is often telogen effluvium, and resolves after approximately five months [ 27 , 28 ]. A proposed hypothesis is that interleukin (IL)-6, an inflammatory cytokine, is involved in hair loss by inhibiting elongation of hair shafts and promoting regression of hair follicles [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of SARS-CoV-2 infection, it has been recently reported AGA may be a risk factor for severe COVID-19, whereas telogen effluvium (TE) presents as a sequela of COVID-19 [ 233 , 234 , 235 ]. In our recent studies [ 236 , 237 ], we have shown that 55.5% COVID-19 patients hospitalized in intensive care unit, 87.5% in ward units or 58.3% seen two months after their hospital discharge exhibited Se plasma concentration below normal range (73–110 µg/L).…”
Section: Oxidative Stress Antioxidants and Aging Hairmentioning
confidence: 99%